The Genealogy of the Political. The Age of Heroes and the Revolt of Youth - Kazlauskas, Raimondas (Sociologija. Mintis ir veiksmas, 2019)
The article discusses the genesis of the political by treating this phenomena as a distinctive interaction between political and religious factors. The aim is to carry out the reconstruction of the premises of the political of ancient Greeks, by distinguishing its particular historic development features, exclusively characteristic for the Ancient Greece context. The rites of passage of Greek social communities are analyzed in order to understand why its youth initiation structure, formed during the Greek Dark Ages, became the basic model for Western Civilisation. The role of youth groups, the phenomena of Greek heroes, the educational structure of the young soldier class (ephebeia), and the first ever political revolution, initiated by Lycurgus, are examined by reconstructing the genealogy of the political.